Missed opportunities for HIV testing in patients newly diagnosed with HIV in Morocco - Latifa Marih; Victoire Sawras; Juliette Pavie; Mustapha Sodqi; Mourad Malmoussi; Noura Tassi; Rajaa Bensghir; Samira Nani; Ahd Oulad Lahsen; Didier Laureillard; Kamal Marhoum El Filali; Karen Champenois; et al. (BMC Infectious Diseases, 2021)
Abstract Background In Morocco, of the estimated 29,000 people living with HIV in 2011, only 20% were aware of their HIV status. More than half of diagnoses were at the AIDS stage. We assumed that people who were unaware of their infection had contacts with the healthcare system for HIV indicators that might prompt the healthcare provider to offer a test. The aim was to assess missed opportunities for HIV testing in patients newly diagnosed with HIV who accessed care in Morocco. Methods A cross-sectional study was conducted in 2012–2013 in six Moroccan HIV centers. Participants were aged ≥18, and had sought care within 6 months after their HIV diagnosis. A standardized questionnaire administered during a face-to-face interview collected the patient’s characteristics at HIV diagnosis, HIV testing and medical history. Contacts with care and the occurrence of clinical conditions were assessed during the 3 years prior to HIV diagnosis. Over this period, we assessed whether healthcare providers had offered HIV testing to patients with HIV-related clinical or behavioral conditions. Results We enrolled 650 newly HIV-diagnosed patients (median age: 35, women: 55%, heterosexuals: 81%, diagnosed with AIDS or CD4 < 200 cells/mm3: 63%). During the 3 years prior to the HIV diagnosis, 71% (n = 463) of participants had ≥1 contact with the healthcare system. Of 323 people with HIV-related clinical conditions, 22% did not seek care for them and 9% sought care and were offered an HIV test by a healthcare provider. The remaining 69% were not offered a test and were considered as missed opportunities for HIV testing. Of men who have sex with men, 83% did not address their sexual behavior with their healthcare provider, 11% were not offered HIV testing, while 6% were offered HIV testing after reporting their sexual behavior to their provider. Conclusions Among people who actually sought care during the period of probable infection, many opportunities for HIV testing, based on at-risk behaviors or clinical signs, were missed. This highlights the need to improve the recognition of HIV clinical indicators by physicians, further expand community-based HIV testing by lay providers, and implement self-testing to increase accessibility and privacy.